A thioredoxin-mimetic peptide exerts potent anti-inflammatory, antioxidant, and atheroprotective effects in ApoE2.Ki mice fed high fat diet. Issue 2 (13th July 2018) - Canesi, Fanny; Mateo, Véronique; Couchie, Dominique; Karabina, Sonia; Nègre-Salvayre, Anne; Rouis, Mustapha; El Hadri, Khadija
Abstract: Aims: Oxidative stress and inflammation play a pathogenic role in atherosclerosis. Thioredoxin-1 (Trx-1) is an anti-oxidative, anti-inflammatory protein with atheroprotective effects. However, in vivo cleavage of Trx-1 generates a truncated pro-inflammatory protein, Trx-80, which compromises the therapeutic use of Trx-1. Here we analysed whether the thioredoxin-mimetic peptide (TxMP), CB3 might exert anti-oxidative, anti-inflammatory, and atheroprotective effects in ApoE2.Ki mice. Methods and results: We synthesized a small TxMP, Ac-Cys-Pro-Cys-amide, CB3 and characterized its antioxidant and anti-inflammatory effects on cultured peritoneal murine macrophages. CB3 significantly and dose-dependently reduced the level of reactive oxygen species in lipopolysaccharides (LPS)-activated macrophages. In addition, it efficiently lowered LPS-induced inflammatory process through NF-κB inhibition, as evidenced by the reduced secretion of monocyte chemoattractant protein-1, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α by macrophages. Nevertheless, CB3 did not affect cholesterol accumulation in macrophages. A daily-administered dose of 10 µg/g body weight CB3 to ApoE2.Ki mice on high fat diet did not affect plasma of total cholesterol and triglycerides levels but significantly reduced the plasma levels of pro-inflammatory cytokines (IL-33 and TNF-α) and oxidative markers. In contrast, it significantly induced the plasma levels of anti-inflammatory proteins (adiponectin, IL-10). In addition, CB3 reduced the number of pro-inflammatory M1 macrophages in spleen and decreased the ratio of M1/M2 macrophages in atherosclerotic lesion areas. Finally, CB3 significantly reduced the surface area of aortic lesions. Conclusions: Our results clearly showed that similar to the full length Trx-1, CB3 exerts protective effects, by reducing inflammation and oxidative stress in macrophages and in ApoE2.Ki mice. The atheroprotective effect of CB3 opens promising therapeutic approaches for treatment of atherosclerosis.